Tree Invasion - Randy Rodgers (Symphony in the Flint Hills, 2018)
Introduction: No doubt, I stand among those who place great value on trees. As a boy I climbed them, drew them, and explored kid-sized wilderness wherever I could roam in even an acre of them. Perhaps we who live in prairie states value trees more than most. Those roots run deep. (Originally published in the 2010 Symphony in the Flint Hills Field Journal.)